Continuous Determination of Glucose Using a Membraneless, Microfluidic Enzymatic Biofuel Cell - Haroon Khan; Jin Ho Choi; Asad Ullah; Young Ho Kim; Gyu Man Kim (Micromachines, 2020)
In this article, we describe an enzyme-based, membraneless, microfluidic biofuel cell for the continuous determination of glucose using electrochemical power generation as a transducing signal. Enzymes were immobilized on multi-walled carbon nanotube (MWCNT) electrodes placed parallel to the co-laminar flow in a Y-shaped microchannel. The microchannel was produced with polydimethylsiloxane (PDMS) using soft lithography, while the MWCNT electrodes were replicated via a PDMS stencil on indium tin oxide (ITO) glass. Moreover, the electrodes were modified with glucose oxidase and laccase by direct covalent bonding. The device was studied at different MWCNT deposition amounts and electrolyte flow rates to achieve optimum settings. The experimental results demonstrated that glucose could be determined linearly up to a concentration of 4 mM at a sensitivity of 31 mV∙mM−1cm−2.